2020
DOI: 10.12688/f1000research.27544.1
|View full text |Cite
|
Sign up to set email alerts
|

Applications of GIS and geospatial analyses in COVID-19 research: A systematic review

Abstract: Background: Geographic information science (GIS) has established itself as a distinct domain and incredibly useful whenever the research is related to geography, space, and other spatio-temporal dimensions. However, the scientific landscape on the integration of GIS in COVID-related studies is largely unknown. In this systematic review, we assessed the current evidence on the implementation of GIS and other geospatial tools in the COVID-19 pandemic. Methods: We systematically retrieved and reviewed 79 research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 88 publications
(99 reference statements)
0
30
0
Order By: Relevance
“…This is consistent with previous research that reported a low scholarly output from LMICs in different areas of health sciences. [41][42][43][44] In the case of syndemics research, the historical and persistent gaps in research capacities in LMICs are likely to be compounded by the fact that syndemics have been primarily conceptualized and extensively studied by scholars and institutions in highincome countries. It is necessary to increase the research capacities in LMICs with a focus on syndemics, as those countries experience a high burden of infectious and noncommunicable diseases and poor social determinants of health.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous research that reported a low scholarly output from LMICs in different areas of health sciences. [41][42][43][44] In the case of syndemics research, the historical and persistent gaps in research capacities in LMICs are likely to be compounded by the fact that syndemics have been primarily conceptualized and extensively studied by scholars and institutions in highincome countries. It is necessary to increase the research capacities in LMICs with a focus on syndemics, as those countries experience a high burden of infectious and noncommunicable diseases and poor social determinants of health.…”
Section: Discussionmentioning
confidence: 99%
“…While the COVID-19 virus has catalysed an international research effort to create a vaccine in record time (Yong 2020), it also provides an opportunity to facilitate global research using geospatial analyses (Ahasan et al 2020;Fatima et al 2021;Helbich, Browning, and Kwan 2021;Yang et al 2020). Ahasan et al (2020) conduct a systematic review of emerging research of geographic information systems (GIS) and geospatial analyses of COVID-19 across thematic groups with an emphasis on public health and first-order impacts (e.g. environment, socio-economic, health surveillance, spatial pattern analysis of COVID-19, and computer-aided spatial and statistical analysis and modelling).…”
Section: Geospatial Approaches To Second-order Impactsmentioning
confidence: 99%
“…Modifiable Areal Unit Problem) that may result from using spatially aggregated data. Our literature review complements Ahasan et al (2020) and Yang et al (2020) by inspecting the geospatial approaches to examining second-order impacts of COVID-19 generally and to inform the C2M2 project specifically.…”
Section: Geospatial Approaches To Second-order Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of COVID-19 and its rapid spread across the world, spatial analysis has played a significant role in the study and mapping of the spread of the disease [ 10 , 11 ]. Several GIS tools and spatial-analysis techniques have been used to track COVID-19 at multiple levels [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%